JEJAK PERSIA DALAM SASTRA MELAYU - Abdul Hadi W. M. (Media Syari'ah, 2017)
The contribution and the influence of Parsi in Nusantara appears in the prayers, rituals and Sufi trend of thoughts; vocabulary, writing style of a saga, poetry, patterned work history, manners, kanun law and religious treatises, commonly called literary books. Splendor of this highly motivated Parsi influence back to the chronicles in the 15th century AD; territory controlled by Persia Timurid dynasty, which greatly promotes the development of culture and literature. Parsi literary and intellectual fields in general retracing its development peak, while the Arabic literary declined. Meanwhile institutionalization of Islam in Nusantara began to grow in the 13th – 15th century, for example in Samudra Pasai (1272-1516 AD) and Malacca (1400-1511 AD). In this article, it will present four Malay literature that assessed many literary works influenced by Parsi, such as the Taj al-Salatin, Hikayat Amir Hamzah, Hikayat Muhammad Ali Hanafiyah, and the Hikayat Burung Pingai.